The Influence of Leadership Style and Work Environment on The Job Motivation of Finance, Accounting, and Tax Consultants, Moderated by Performance-Based Incentives - Cipta Halim; Hastuti Naibaho; Endi Sarwoko (Cv. Syntax Corporation Indonesia, 2026)
The increasing complexity of financial regulations, accounting standards, and taxation systems has intensified the demand for Finance, Accounting, and Tax (FAT) consultants with high levels of professional competence and sustained work motivation. In professional service organizations, employee motivation is influenced not only by individual capabilities but also by leadership practices, the work environment, and reward systems. This study aimed to examine the influence of leadership style and the work environment on the work motivation of FAT consultants while analyzing the moderating role of performance-based incentives. This research employed a quantitative survey design involving 53 FAT consultants at KJA CTO Consulting. Data were collected using a Likert-scale questionnaire and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS) using SmartPLS software. The results indicated that leadership style had a positive and statistically significant effect on work motivation, demonstrating that effective leadership characterized by clear direction, effective communication, support, and fairness contributed to higher consultant motivation. The work environment had a positive but statistically insignificant effect when evaluated simultaneously with the other variables. Meanwhile, performance-based incentives exerted the strongest positive influence on work motivation, indicating that transparent and performance-oriented reward systems enhanced consultant motivation. The moderation analysis revealed that performance-based incentives tended to strengthen the relationship between leadership style and work motivation; however, the moderating effect was not statistically significant. This study concluded that leadership quality and performance-based incentives were the primary factors influencing the work motivation of FAT consultants and that organizations should continue to strengthen leadership development and performance-based incentive systems.